Impacto del control de inventarios en la gestión financiera del emprendimiento “Industria Maderera Viscarra”, de la ciudad de Guaranda durante el período enero diciembre del 2020. - Galeas Gavilánez, Kathy Shajaira (2021)
It is a priority for the companies that are dedicated to the commercialization of articles the adoption and management of standards and policies established in the business such as the mechanisms and practices of inventory control that support an efficient management in the operations; therefore, the primary objective of the study was to determine the impact of inventory control on the financial management of the enterprise "Industria Maderera Viscarra"; contrasting the degree of incidence of optimal control of product items on both economic and financial resources. The methodology used involved a field study supported by primary sources such as observation, interviews, surveys, and secondary sources such as similar research, texts, and complementary bibliography. The field work allowed an inductive approach to be made under the premise of the particularities to the generalities; therefore, the description of the main results denoted a manual empirical control through booklets, ignorance of the minimum and maximum stock, loss of customers, absence of inventory policies, inappropriate inventory rotation. Under the specified precision regarding the information collected, the hypothesis was verified in a descriptive way. Under the full identification of the requirement of an Inventory Control System, we proceeded with the proposal of the EVA ERP software. The aforementioned system allowed to exercise a personalized control by product items, incorporated the transcript cards under the Weighted Average valuation method, yielded the final inventories that linked to financial management allowed to know the rotation of the products.